2019
DOI: 10.1002/iroh.201801958
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic N in shallow tropical lakes and reservoirs: Contribution to total dissolved N and relationships with eutrophication

Abstract: Dissolved organic nitrogen (DON) plays important biogeochemical and ecological roles in aquatic systems. However, little is known about its importance in small tropical lakes and reservoirs. We hypothesized that (a) DON is higher in these systems than dissolved inorganic N (DIN), and that (b) relative contributions of DON and DIN to the total dissolved nitrogen (TDN) pool decrease and increase, respectively, with trophic status. To test these hypotheses, we measured DON and DIN in six lakes and two reservoirs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…These results suggested that the concentration of approximately 8 mg l -1 was the maximum threshold of M. densa for N demand. This concentration was significantly higher than the N concentration in most lakes and reservoirs [35,36], which suggested that M. densa could grow rapidly in most waters and N concentrations in natural waters would not restrict the growth of M. densa.…”
Section: P (Mg L -1 )mentioning
confidence: 88%
“…These results suggested that the concentration of approximately 8 mg l -1 was the maximum threshold of M. densa for N demand. This concentration was significantly higher than the N concentration in most lakes and reservoirs [35,36], which suggested that M. densa could grow rapidly in most waters and N concentrations in natural waters would not restrict the growth of M. densa.…”
Section: P (Mg L -1 )mentioning
confidence: 88%
“…"> 2.Major drivers of extensive DO deficits. The metabolism of shallow turbid reservoirs under chronic eutrophication is still poorly known (Cuker et al, 1990), and improved understanding is needed to inform more protective management decisions (e.g., Andrzej et al, 2002; Boëchat et al, 2019; Dadi et al, 2017). Is the extensive anoxia/hypoxia in this system being driven primarily by present system production, and/or allochthonous carbon inputs, and/or past production (sediment consumption), or other factor(s)?…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of tropical reservoir that are impacted by eutrophication are: Guarapiranga reservoir, in the State of São Paulo -Brazil (Alcantara et al, 2021) and Barra Bonita reservoir, also in the State of São Paulo -Brazil (Watanabe et al, 2015). Also, Boëchat et al (2019) studied six shallow lakes and two reservoirs at the Atlantic forest in Southeastern Brazil and determined hypereutrophic state to lake Rasa and Pampulha Reservoir.…”
Section: Physicochemical Parametersmentioning
confidence: 99%